Penggunaan Metode Permainan dalam Pembelajaran Bahasa Arab untuk Meningkatkan Motivasi dan Partisipasi Siswa Kelas XI MQNH PUTRI - Parihin Parihin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2023)
This research is to explore the impact of using a game-based approach on student motivation and participation in the Arabic language learning process. By conducting an in-depth analysis of classroom dynamics, level of student engagement, and learning outcomes, this research reveals the positive impact of game integration in the learning process. The research results show that the game method effectively creates an interactive and enjoyable learning environment, thereby increasing student motivation and reducing uncertainty in the classroom. Through active participation in various game activities, students have practical opportunities to apply Arabic language skills in real situations, thereby increasing language competence and confidence in language use. Although some challenges such as time allocation and complex assessment were identified, the long-term benefits of this approach were seen in improving students' language understanding and skills. Therefore, this study supports the integration of game methods in the Arabic curriculum, emphasizing the importance of adapting it to suit the needs and dynamics of the classroom. The findings from this research provide a basis for developing innovative learning strategies that focus on students, with the aim of improving more effective Arabic language learning outcomes in class XI MQNH.